How Does the Relationship between Self-Awareness and Self-Efficacy with Career Decision-Making of High School Students? - Cahyaningtyas, Dita; Kholili, Ma`rifatin Indah; Dewantoro, Adi (Pamomong: Journal of Islamic Educational Counseling, 2023)
This study analyzes the relationship between self-awareness and self-efficacy in career decision-making. The research approach used is quantitative with a correlational method. The sampling technique employs proportional random sampling, with a sample size of 72 students. Data collection techniques use psychological scales. The instruments used are self-awareness, self-efficacy, and decision-making psychology scales, which the researcher developed. The results of this study are as follows: 1) On average, students have moderate levels of self-awareness and self-efficacy and high levels of career decision-making; 2) There is a positive relationship between self-awareness and career decision-making, with an obtained value of r = 0.407 (p= 0.000; p<0.05); 3) There is a non-significant relationship between self-efficacy and career decision-making, with a value of r = 0.038 (p= 0.751; p>0.05); 4) Simultaneously, there is a significant positive relationship with a moderate correlation level between self-awareness and self-efficacy with career decision-making, with an obtained value of R = 0.409 (p= 0.002; p<0.05). Overall, the results of this study indicate that the higher the self-awareness and self-efficacy, the higher the students’ career decision-making, and vice versa.